2008
DOI: 10.1523/jneurosci.3063-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Processing of Uncertain Information in Visuomotor Control

Abstract: Our sensory observations represent a delayed, noisy estimate of the environment. Delay causes instability and noise causes uncertainty. To deal with these problems, theory suggests that the processing of sensory information by the brain should be probabilistic: to start a movement or to alter it midflight, our brain should make predictions about the near future of sensory states and then continuously integrate the delayed sensory measures with predictions to form an estimate of the current state. To test the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 33 publications
(37 reference statements)
5
98
1
Order By: Relevance
“…Optimal dynamic state estimation is thought to be the result of combining state predictions with delayed sensory feedback (Gritsenko et al 2009;Izawa and Shadmehr 2008;Wolpert et al 1995), a process that is dependent on the posterior parietal cortex and cerebellum (Bastian 2006;Miall et al 2007;Miall and King 2008;Shadmehr and Krakauer 2008). Previous research has demonstrated structural changes in both the parietal cortex and cerebellum across the age range examined in the current study (Giedd et al 1999;Tiemeier et al 2010).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Optimal dynamic state estimation is thought to be the result of combining state predictions with delayed sensory feedback (Gritsenko et al 2009;Izawa and Shadmehr 2008;Wolpert et al 1995), a process that is dependent on the posterior parietal cortex and cerebellum (Bastian 2006;Miall et al 2007;Miall and King 2008;Shadmehr and Krakauer 2008). Previous research has demonstrated structural changes in both the parietal cortex and cerebellum across the age range examined in the current study (Giedd et al 1999;Tiemeier et al 2010).…”
Section: Discussionmentioning
confidence: 78%
“…Thus predicting future states based on efference copies of motor commands can be used as an internal reference to circumvent processing delays, a finding that has been demonstrated in adults (Desmurget and Grafton 2000;Tseng et al 2007;Wagner and Smith 2008;Wolpert and Flanagan 2001). This prediction can be combined with sensory feedback to provide an up-to-date, online state estimate (i.e., dynamic state estimation) (Izawa and Shadmehr 2008;Vaziri et al 2006;Wolpert et al 1995). The development of dynamic state estimation across childhood has not, to our knowledge, been investigated.…”
mentioning
confidence: 99%
“…After the discharge reaches a threshold, monkeys start the motor response. The hypothesis that the process of accumulating information must reach a threshold before initiation of action also accounts for the finding that human participants start their movements later when they are less certain of the exact location of the target (Izawa and Shadmehr, 2008).…”
Section: On-line Processing Of Uncertain Informationmentioning
confidence: 91%
“…An alternative view is that the new estimated target position is a weighted combination of the first and second targets. Izawa and Shadmehr (2008) tested this hypothesis by asking participants to reach toward a blurry target that occasionally jumped during the reach. Consistent with the probabilistic model, they found that the motor response to the second target was influenced by the uncertainty about the first target.…”
Section: On-line Processing Of Uncertain Informationmentioning
confidence: 99%
“…However, experiments suggest that the brain alters sensitivity to error based on its uncertainty about its predictions relative to its uncertainty about observations (Burge et al 2008;Korenberg and Ghahramani 2002). For example, when visual feedback about the consequences of a movement is blurry, one is less likely to change their motor commands compared with when it is sharp (Izawa and Shadmehr 2008). Even when the quality of the sensory feedback is kept constant, the brain appears to modulate sensitivity to error as a function of error size.…”
mentioning
confidence: 99%